Open circuit fault detection and diagnosis on matrix converter systems - Zhang, Jiawei (2019)
Matrix converters have received continued research attention as a result of their possibility of higher power density, controllable input power factor, and removal of DC-Link component. However due to the numerous semiconductor power switches used in such circuits there is a high possibility of switch failures.